Foldable semi-ladder polymers: novel aggregation behavior and high-performance solution-processed organic light-emitting transistors. Issue 41 (1st October 2020) - Yuan, Dafei; Awais, Mohammad A.; Sharapov, Valerii; Liu, Xunshan; Neshchadin, Andriy; Chen, Wei; Bera, Mrinal; Yu, Luping
Abstract : Coiled foldamers with intramolecular H-aggregation in semi-ladder copolymers lead towards the highest EQE of 6.9% in solution-processed multi-layer OLETs. Abstract : A critical issue in developing high-performance organic light-emitting transistors (OLETs) is to balance the trade-off between charge transport and light emission in a semiconducting material. Although traditional materials for organic light-emitting diodes (OLEDs) or organic field-effect transistors (OFETs) have shown modest performance in OLET devices, design strategies towards high-performance OLET materials and the crucial structure–performance relationship remain unclear. Our research effort in developing cross-conjugated weak acceptor-weak donor copolymers for luminescent properties lead us to an unintentional discovery that these copolymers form coiled foldamers with intramolecular H-aggregation, leading to their exceptional OLET properties. An impressive external quantum efficiency (EQE) of 6.9% in solution-processed multi-layer OLET devices was achieved.